Synthesis Strategies and Structural Design of Porous Carbon‐Incorporated Anodes for Sodium‐Ion Batteries. Issue 6 (22nd May 2019) - Wang, Enhui; Chen, Mingzhe; Guo, Xiaodong; Chou, Shu‐Lei; Zhong, Benhe; Dou, Shi‐Xue
Abstract: Over the past decades, porous carbonaceous and carbon‐incorporated composites have aroused tremendous attention owing to their unique properties such as high surface area, excellent accessibility to active sites, tunable morphologies and structures, and superior mass transport and diffusion. They have been widely investigated and applied in various fields, such as energy storage, absorption, water filtration, drug delivery, catalysis, and sensing. In the energy storage area, rechargeable sodium‐ion batteries (SIBs) have attracted tremendous attention as the next‐generation power plants for large‐scale energy storage systems (EESs). However, their low energy density and power density, as well as their poor cyclability, are still the main challenges for SIBs, especially for the anode, which acts as a bottleneck. With the incorporation of appropriate porous carbonaceous materials, the disadvantages of large volume shrinkage and low electron conductivity of alloying‐ and conversion‐based anode materials have been significantly alleviated. This review points out and summarizes the most recent developments in synthesis strategies and morphology control of porous carbonaceous materials and the corresponding carbonaceous‐material‐incorporated high performance anodes for SIBs. Furthermore, the remaining challenges associated with these composites and effective routes to enhance their performance are discussed. Abstract : The morphology designs and synthesis strategies for carbonaceous incorporated anode materials of sodium‐ion batteries are comprehensively and systematically summarized. This review points out and summarizes the most recent developments in synthesis strategies and morphology control of porous carbonaceous materials and the corresponding carbonaceous‐material‐incorporated high‐performance anodes for sodium‐ion batteries.